1999
DOI: 10.1007/bf03161689
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of soil organic matter in freshwater emergent/open water wetlands in the Portland, Oregon metropolitan area

Abstract: Abstract:We measured soil organic matter (SOM) concentrations in a large sample ~n = 95) of freshwater emergent and open water weltands in the Portland, Oregon, USA, ,area as part of a study of the ecological development of mitigation wetlands. Mean SOM concentrations were higher in naturally occurring wetlands (NOWs) than in mitigation wetlands (MWs) at 0-5 cm (SOM = 9.75 and 5.83%, respectively, p = 0.0001) and at 15-20 cm (SOM = 6.85, 4.68%, p = 0.0551). If temporal accumulation of SOM is occurring, it is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 26 publications
4
31
2
Order By: Relevance
“…Agricultural activity in hydric soils does not always result in the depletion of soil organic carbon (Shaffer and Ernst, 1999). In our study, it was shown that the wetness of the soil, which was influenced by the position in the dambo, had an effect on total organic content ( Figure 5) since organic carbon increased with an increase in moisture content.…”
Section: Discussionmentioning
confidence: 55%
“…Agricultural activity in hydric soils does not always result in the depletion of soil organic carbon (Shaffer and Ernst, 1999). In our study, it was shown that the wetness of the soil, which was influenced by the position in the dambo, had an effect on total organic content ( Figure 5) since organic carbon increased with an increase in moisture content.…”
Section: Discussionmentioning
confidence: 55%
“…Because of its importance as an indicator of biogeochemical processing, the status of soil organic matter accumulation has become an important consideration in assessing the success of wetland restoration projects (Craft et al 1988(Craft et al , 1999. It is generally assumed that organic matter levels will increase with time of recovery in restored wetlands (Craft et al 1988(Craft et al , 1999 and that, initially, organic matter levels are lower in restored or created wetlands than in natural (control) wetlands (Bischel-Machung et al 1996, Shaffer & Ernst 1999. In the present study, we found that this simple relationship does not adequately describe soil organic matter content in control versus managed swamps; RIM swamps had more than twice as much soil organic matter than both control and restored (breached-RIM) mangals (Table 3).…”
Section: Soil Developmentmentioning
confidence: 99%
“…Data collection and data analysis approaches can be found in previously published regional guidebooks (http://el.erdc.usace.army.mil/wetlands/guidebooks.html) as well as peer-refereed publications that have characterised subclasses in such a way that the natural variability is determined (Magee et al 1999;Rheinhardt et al 1999;Shaffer and Ernst 1999). Techniques for data collection are not unique to the HGM approach, but rather are common ecological sampling methods for forests and grasslands with emphasis on hydrologic indicators.…”
Section: Development Of Models Of Functions Variables and Indicatorsmentioning
confidence: 99%